2021
DOI: 10.1038/s41598-021-83311-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature on the behaviour and metabolism of an intertidal foraminifera and consequences for benthic ecosystem functioning

Abstract: Heatwaves have increased in intensity, duration and frequency over the last decades due to climate change. Intertidal species, living in a highly variable environment, are likely to be exposed to such heatwaves since they can be emerged for more than 6 h during a tidal cycle. Little is known, however, on how temperature affects species traits (e.g. locomotion and behaviour) of slow-moving organisms such as benthic foraminifera (single-celled protists), which abound in marine sediments. Here, we examine how tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 111 publications
3
15
0
Order By: Relevance
“…Several studies have reported that increasing pore water temperatures can cause adverse effects to intertidal foraminifera (i.e. reduce locomotion, metabolism and reproduction (Buzas & Severin, 1993; Gross, 2000; Wukovits et al ., 2017; Li et al ., 2019; Deldicq et al ., 2021). On a regional scale, cooler water temperatures are known to favour the preservation of agglutinated tests compared with warmer regions and tropical environments such as mangroves (Goldstein & Watkins, 1999; Debenay et al ., 2002; Berkeley et al ., 2009 a ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that increasing pore water temperatures can cause adverse effects to intertidal foraminifera (i.e. reduce locomotion, metabolism and reproduction (Buzas & Severin, 1993; Gross, 2000; Wukovits et al ., 2017; Li et al ., 2019; Deldicq et al ., 2021). On a regional scale, cooler water temperatures are known to favour the preservation of agglutinated tests compared with warmer regions and tropical environments such as mangroves (Goldstein & Watkins, 1999; Debenay et al ., 2002; Berkeley et al ., 2009 a ).…”
Section: Discussionmentioning
confidence: 99%
“…During the sampling period, temperature has increased from ~7°C (February) to ~18°C (June), which may have induced a seasonal effect on the organism' activity as evidenced for macrofaunal species (Pascal et al 2019). A recent study on Haynesina germanica showed however, that foraminiferal SSRRi has a low thermal dependence in the range 6-24°C (Deldicq et al 2021). In this study, we assume that the potential seasonal effect could be negligible through the use of an acclimation period carried out before running the experiment.…”
Section: Sediment Sampling and Experimental Set-upmentioning
confidence: 99%
“…Low-volume training requires subjects to train for 2 to 3 hours a day. 3 In this study, the second training day of the two training weeks was selected as the study content, and the following day after training was used as the recovery period.…”
Section: Test Proceduresmentioning
confidence: 99%